2015
DOI: 10.1016/j.bcp.2015.08.083
|View full text |Cite
|
Sign up to set email alerts
|

High affinity α3β4 nicotinic acetylcholine receptor ligands AT-1001 and AT-1012 attenuate cocaine-induced conditioned place preference and behavioral sensitization in mice

Abstract: Cholinergic signaling via the nicotinic acetylcholine receptors (nAChRs) in the mesolimbic circuitry is involved in the rewarding effects of abused drugs such as cocaine and opioids. In mouse studies, nonselective nAChR antagonist mecamylamine blocks cocaine-induced conditioned place preference (CPP) and behavioral sensitization. Among subtype-selective nAChR antagonists, the β2-selective antagonist dihydrobetaerythroidine and α7 nAChR antagonist methyllycaconitine (MLA), but not MLA alone prevent behavioral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 53 publications
(75 reference statements)
0
15
0
Order By: Relevance
“…Work from Fowler and Kenny demonstrated that α5-KO (α5-expressing nAChRs are enriched in the vMHb-IPN pathway) mice show escalations of nicotine self-administration through a blunting of the aversive properties of nicotine and not an increase in the rewarding aspects of the drug (Fowler & Lu Qun 2011;Tuesta et al 2011). Conversely, pharmacological antagonism of β4-expressing nAChR (also enriched in the vMHb-IPN pathway) inhibits the self-administration of morphine and cocaine and blocks the formation of cocaine CPP (Glick et al 2006;McCallum & Glick 2009;Khroyan et al 2015). It is likely that a balance between α5 and β4 subunits is more influential in regulating drug response than a single subunit (Frahm et al 2011; ChAT-Cre DIO-mCherry-infused mice acquire cocaine-induced CPP (2-way ANOVA, main effect of conditioning, F 1,9 = 30.56, p = 0.0004), with no differences between CNO-primed (n = 6) and Veh-primed (n = 5) animals (no effect main effect of CNO-priming (F 1,9 = 0.4273, p = 0.5297).…”
Section: Discussionmentioning
confidence: 99%
“…Work from Fowler and Kenny demonstrated that α5-KO (α5-expressing nAChRs are enriched in the vMHb-IPN pathway) mice show escalations of nicotine self-administration through a blunting of the aversive properties of nicotine and not an increase in the rewarding aspects of the drug (Fowler & Lu Qun 2011;Tuesta et al 2011). Conversely, pharmacological antagonism of β4-expressing nAChR (also enriched in the vMHb-IPN pathway) inhibits the self-administration of morphine and cocaine and blocks the formation of cocaine CPP (Glick et al 2006;McCallum & Glick 2009;Khroyan et al 2015). It is likely that a balance between α5 and β4 subunits is more influential in regulating drug response than a single subunit (Frahm et al 2011; ChAT-Cre DIO-mCherry-infused mice acquire cocaine-induced CPP (2-way ANOVA, main effect of conditioning, F 1,9 = 30.56, p = 0.0004), with no differences between CNO-primed (n = 6) and Veh-primed (n = 5) animals (no effect main effect of CNO-priming (F 1,9 = 0.4273, p = 0.5297).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that AT-1001 does not exhibit reinforcing properties per se and does not induce reinstatement of nicotine seeking in extinguished rats [32, 36]. We have also shown that AT-1001 does not induce a conditioned place preference or aversion in mice [51]. …”
Section: Discussionmentioning
confidence: 99%
“…In this latter study, the involvement of α6β2-containing nAChRs was confirmed pharmacologically by the blockade of cocaine reward with the intracerebral administration of the selective nAChR antagonist α-conotoxin MII. Other nAChR-regulated brain circuits may also be involved in cocaine reward, since the high affinity α3β4 nAChR functional antagonists, AT-1001 and AT-1012, can also attenuate cocaine place preference (183). A less selective α3β4 nAChR antagonist, 18-methoxycoronaridine, has also been shown to inhibit the self-administration of both cocaine and methamphetamine (184,185).…”
Section: Concurrent Use Of Nicotine and Psychostimulantsmentioning
confidence: 99%